2021
DOI: 10.1088/1755-1315/923/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Different Levels of Turmeric Root Powder and Carnation Flowers to The Diet on Some Blood and Microorganisms Traits of Broilers Under Heat Stress Condition

Abstract: The current study was carried out on a poultry farm which belongs to the Animal production department - College of Agriculture - University of Kufa, for a period of 35 days started from October 10 to November 13, 2020 for 5 weeks to find out the effect of adding different levels of turmeric root powder and carnation flowers to the diet on some productive traits of broilers. in the experiment, 360 broiler chicks were used, one-day-old Ross-308 hybrid, The chicks were divided randomly into 6 treatments (60 chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Fat oxidation and decreased serum MDA concentration, which is used as an indicator of the degree of lipid oxidation. This may be an indication of a decrease in heat stress exposed to the birds of transactions fed on a diet containing okra fruits powder and seeds containing the active substances, which led to a decrease in oxidative stress indicated by the increase in the concentration of SOD and the decrease in the concentration of MDA for the birds of these treatments, where the H/L ratio is considered an indication over stress [20,21]. The results also showed that there was an effect of adding okra fruits and seeds powder to the diet on the concentration of glucose, total protein, albumin, globulin, yolk, and cholesterol in the serum of broiler chickens subjected to heat stress (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Fat oxidation and decreased serum MDA concentration, which is used as an indicator of the degree of lipid oxidation. This may be an indication of a decrease in heat stress exposed to the birds of transactions fed on a diet containing okra fruits powder and seeds containing the active substances, which led to a decrease in oxidative stress indicated by the increase in the concentration of SOD and the decrease in the concentration of MDA for the birds of these treatments, where the H/L ratio is considered an indication over stress [20,21]. The results also showed that there was an effect of adding okra fruits and seeds powder to the diet on the concentration of glucose, total protein, albumin, globulin, yolk, and cholesterol in the serum of broiler chickens subjected to heat stress (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in MDA concentration in animals fed vitamin C is due to the role of the vitamin as an antioxidant that reduces oxidative stress. This is indicated by an increase in the concentration of the GPX enzyme, as well as due to vitamin C activity in reducing body temperature and rapid breathing, thus reducing oxidative stress generated by birds being exposed to heat stress [32][33][34].…”
Section: Oxidation Enzymesmentioning
confidence: 99%
“…Conversely, 0.5% turmeric powder did not have any impact on growth and caused an enormous decline in the feed conversion ratio; however, it could improve thyroid hormones, increase feed intake, and reduce blood MDA and lipid peroxidation in the heat-stress broiler [ 98 , 99 ]. Moreover, the addition of turmeric root powder, as well as its mixture with carnation flowers, to the diet of broilers under heat stress conditions showed an increase in the percentage of lymphocytes and the concentration of total protein and globulin; meanwhile, while the levels of glucose and uric acid and the number of harmful bacteria were declined [ 100 ]. Correspondingly, the 8 g/kg diet of C. longa powder also resulted in better intestinal morphology under hot tropical environments, leading to the amelioration of nutrient absorption and thermotolerance of broiler chickens [ 11 ].…”
Section: Curcumin In Stress Management Of Avianmentioning
confidence: 99%